Clinical Profile Of Gestants With Threat Of Preterm Delivery That Concludes In Preterm Birth - Castillo-Castro, Evert (2017)
Objective. To describe the clinical profile of pregnant women with a threat of preterm delivery who conclude in preterm birth. Material and methods. Observational and descriptive study. Forty-six pregnant women from 24 to <37 weeks of gestation participated with the threat of preterm labor, whose gestation ended in preterm labor, attended at the maternity service of the Hospital Víctor Lazarte Echegaray-Essalud de Trujillo during the period May to October 2015.